Reaction of Sulphene with 2-Hydroxyphenylethylideneanilines and Evaluation of the Products for Fungitoxicity - SINGH, C.P.; HASAN, HAMID (Asian Journal of Chemistry, 2010)
Addition of sulphene, generated in situ from the reaction of methanesulphonylchloride and triethylamine, to 2-hydroxy-phenylethylideneaniline and its N-phenyl derivatives (I-V) resulted in the formation of cycloadducts (la-Va). The crude products were recrystallized from ethanol. Elemental analysis of the products checks well with 1 : 1 addition product. On the basis of spectral studies, the products have been assigned 1,4-benwthiazine structure. The synthesized 1,4-benzothiazines (la-Va) were tested against Alternaria alternata, Curvularia lunata, Fusarium oxysporum and Myrothecium roridum for their antifungal activity by spore germination inhibition method at various concentrations. Some of the compounds have shown promising antifungal activity.